A case of pituitary metastasis of lung cancer associated with panhypopituitarism and cerebral neuropathy requiring differentiation from granulomatosis with polyangiitis - Hayashi, Chiga; Ohmura, Shin-ichiro; Miwa, Hideki; Yonezawa, Haruka; Otsuki, Yoshiro; Miyamoto, Toshiaki; Morishima, Saki; Watahiki, Motoi; Kawaji, Hiroshi; Sugimura, Yoshihisa (Clinical Rheumatology and Related Research, 2024)
A 86-year-old woman who was diagnosed with granulomatosis polyangiitis（GPA）2 years ago developed lung adenocarcinoma（Stage IA）but she was successfully treated with radiation therapy and remained in remission. After 3 months of the radiation therapy, pituitary enlargement with panhypopituitarism developed, and the patient was treated with high-dose glucocorticoids for GPA with this lesion. However, the lesion did not improve after the treatment. Finally, she underwent pituitary biopsy and pituitary biopsy showed pituitary metastasis of lung cancer. Our case indicated that aggressive histological evaluation is very important in GPA patients with pituitary lesions.